PENGARUH PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS IV PADA MATERI ENERGI PANAS - Nurfillah, Anisa; Panjaitan, Regina Lichteria; Nuraeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
The purpose of this research is to know the science process skills improvement students learning model by using inkuiri on thermal energy of matter in class IV SDN Bangkir and SDN Parakanmuncang I. The research is used a method of pre-experimentals with one groupz pretest posttest designs research. The instruments test used in basic ability of IPA (KAIPA), test of science process skills. The results of this research show the results of calculation of average difference test pretest and posttest high group by using paired t-test, for medium group by using the wilcoxon test, and for low group by using a paired t-test that shows the results of the p-value (Sig) 0.000 which means that p-value significance level Î± Î± = 0.05 indicates an increase in science process skills students in the high group , medium and low group learning model by using inkuiri.